Catalytic Processes for CO2 Utilization - Lehner, Markus; Karl, Juergen; Rauch, Reinhard (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In addition to the avoidance and long-term storage (CCS) of anthropogenic CO2 emissions, the utilization of CO2 for the production of usable products is discussed as a possible method of reducing greenhouse gas emissions. The associated technologies are summarized under the term "Carbon Capture and Utilization" (CCU). CCU technologies have gained increasing attention in science and industry over the last decade and are considered essential for meeting the reduction goals of the Paris Agreement. The selection of research papers in this book, mostly focused on Power-to-X technologies and the catalytic conversion of CO2, are related to the most recent advancements in CCU technologies.